2005
DOI: 10.1029/2005eo190001
|View full text |Cite
|
Sign up to set email alerts
|

Space‐based measurement of river runoff

Abstract: Observations of river inundation areas, water levels, and flow variability from orbital sensors have the potential to directly measure the runoff component of the Earth's hydrologic cycle [Birkett et al., 2002; Brakenridge et al., 1998; Sippel et al., 1994, 1998; Townsend, 2001]. A remote‐sensing‐based measurement strategy for rivers and streams is emerging: Surface water data can be collected, their accuracy evaluated, and the results disseminated without regard to political boundaries. The results can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 15 publications
0
87
0
Order By: Relevance
“…[46,47]). At the same time, Earth systems science has developed a rapidly expanding arsenal of data products including those from remote sensing, ground-based hydrometeorological networks, data assimilation and simulation that could be used to monitor and analyse the nature of extreme weather over large domains [48][49][50]. Many datasets are global in extent yet at resolutions useful in monitoring local environmental conditions [51] and supporting flood early warning systems [48].…”
Section: Methodsmentioning
confidence: 99%
“…[46,47]). At the same time, Earth systems science has developed a rapidly expanding arsenal of data products including those from remote sensing, ground-based hydrometeorological networks, data assimilation and simulation that could be used to monitor and analyse the nature of extreme weather over large domains [48][49][50]. Many datasets are global in extent yet at resolutions useful in monitoring local environmental conditions [51] and supporting flood early warning systems [48].…”
Section: Methodsmentioning
confidence: 99%
“…Although the monitoring infrastructure is largely in place (Hannah et al 2011), continued difficulty in attracting funding and fostering international cooperation are major obstacles even though traditional in situ networks are much cheaper than satellite platforms. Remote sensing capabilities to estimate riverine water fluxes have been discussed by a number of authors (Alsdorf and Lettenmaier 2003;Alsdorf et al 2007;Andreadis et al 2007;Brakenridge et al 2005). Recently, proposed calculation of fresh water fluxes from the continents, based on satellite-measured precipitation and evaporation over the ocean in conjunction with sea level measurement.…”
Section: Hydrological Cyclementioning
confidence: 99%
“…Brakenridge et al (2005) demonstrated that AMSR-E can measure river discharge changes in various climatic conditions. The methodology uses the brightness temperature at 36.5 GHz H-polarization during the descending (night) orbit of AMSR-E with a footprint size of approximately 8 6 12 km 2 and an average revisit time at 1 day.…”
Section: De Groevementioning
confidence: 99%